Post-Kolonialisme Perkembangan Peradaban dan Filsafat Pendidikan Islam - Nurhalim Nurhalim; Ilzamudin Ma’mur; Agus Gunawan; Ahmad B Syam (Indonesian Journal of Social Science Education (IJSSE), 2023)
Post-colonialism is still a debate and an interesting phenomenon, as the development of civilization cannot be separated from education. This research aims to determine the development of post-colonial civilization from the standpoint of educational philosophy. This study uses a qualitative method, a literary approach sourced from books and journals, and thematic analysis. The development of post-colonial civilization still creates westernized thinking. From the Islamic perspective, religion is separated from other fields or secularism. The secular education system was formed due to colonialism in most Muslim-majority countries. They are reconstructing Islamic education's philosophy on a gradual and sustainable education transformation and prioritizing religious moderation in Indonesia. The post-colonial perspective can create an Islamic education system. It is oriented towards developing an Islamic worldview as an enlightening civilization. The implications of an Islamic education system based on religious moderation and enlightenment can help a civilization develop while avoiding new colonialism.